Современное разнообразие Charales озера Свитязь (Шацкий национальный природный парк, Волынское Полесье, Украина) - Борисова, Е.В.; Царенко, П.М.; Якушенко, Д.Н. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2008)
Представлены результаты исследования видового состава Charales оз. Свитязь (Шацкий НПП, Волынское Полесье, Украина), проведенного в 2006 г. В настоящее время в оз. Свитязь произрастает семь видов харовых водорослей: Chara aculeolata Kütz. in Rchb., Ch. aspera Dethard. ex Willd., Ch. contraria A. Braun ex Kütz., Ch. delicatula C. Agardh, Ch. fragilis Desv. in Loisel., Nitella syncarpa (Thuill.) Chev. и Nitellopsis obtusa (Desv. in Loisel.) J. Groves. Приведены некоторые сведения об их экологии и биологии. Анализ оригинальных и литературных данных выявил изменение видового состава Charales оз. Свитязь по сравнению с 50-ми годами прошлого столетия. Общее количество видов увеличилось. При этом во флоре озера появилось пять новых видов и исчез один – редкий для Украины Ch. polyacantha A. Braun in A. Braun, Rabenh. et Stitzenb. Значительно сократилась площадь произрастания ранее доминирующего Ch. delicatula (занесенного в "Красную книгу Украины"). Вместо него массово стали развиваться Ch. aspera – на песчаных и N. obtusa – на илистых и торфянисто-илистых донных отложениях. Увеличение видового разнообразия Charales оз. Свитязь рассматривается как реакция данной группы водорослей на антропогенную трансформацию, связанную с хозяйственной деятельностью и рекреацией. The Charales species composition of Lake Svitiaz (Shatsk National Natural Park, Volyn Polissia, Ukraine) studied in 2006 is presented. Now there are seven species of characean algae namely Chara aculeolata Kütz. in Rchb., Ch. aspera Dethard. ex Willd., Ch. contraria A. Braun ex Kütz., Ch. delicatula C. Agardh, Ch. fragilis Desv. in Loisel., Nitella syncarpa (Thuill.) Chev. and Nitellopsis obtusa (Desv. in Loisel.) J. Groves. Also some ecological and biological data of founded species are given. A comparative analysis of original data and previous information of other authors gives evidence to some changes in the Charales species composition of Lake Svitiaz which has occurred since 50-years last century. Five new species were founded in the flora of Lake Svitiaz but Ch. polyacantha A. Braun in A. Braun, Rabenh. et Stitzenb., the rare species for Ukraine, was vanished. An area of the Ch. delicatula population, Ukrainian Red Book species, which was predominated in the past strongly reduced. Instead of it a development of the populations of Ch. aspera on sand bottom sediments and of N. obtusa on silt and silt-peaty ones was founded. An increase of the Charales species diversity is considered as a response of these algae to an anthropogenic transformation caused by agricultural activities and recreation.